How Far are Students’ Science Thinking in Inquiry Learning? - Dewi, Pramita Sylvia; Widodo, Ari; Rochintaniawati, Diana; Prima, Eka Cahya (Indonesian Journal of Science and Mathematics Education, 2023)
This study aims to identify science learning activities for junior high school students. The research design is descriptive and quantitative. The sample in this study was 38 students, and the questions tested consisted of 28 items analyzed by Rasch analysis. Question items are correct if students can answer questions according to their guided inquiry abilities. The results showed that almost all samples could not participate in science learning using guided inquiry. Of the 28 questions tested on students, only three had a score above 50%, and the rest were almost, on average, below 50%. It can be concluded that students have yet to realize that guided inquiry is the essence of science learning, which helps them conduct and develop science learning in the classroom. This study recommends the application of guided inquiry to students to be able to harmonize thinking in science learning in junior high school.